2023
DOI: 10.1038/s42005-023-01449-w
|View full text |Cite
|
Sign up to set email alerts
|

Collective mechano-response dynamically tunes cell-size distributions in growing bacterial colonies

René Wittmann,
G. H. Philipp Nguyen,
Hartmut Löwen
et al.

Abstract: Mechanical stresses stemming from environmental factors are a key determinant of cellular behavior and physiology. Yet, the role of self-induced biomechanical stresses in growing bacterial colonies has remained largely unexplored. Here, we demonstrate how collective mechanical forcing plays an important role in the dynamics of the cell size of growing bacteria. We observe that the measured elongation rate of well-nourished Escherichia coli cells decreases over time, depending on the free area around each indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 103 publications
1
5
0
Order By: Relevance
“…To emphasise the generic mechanical nature of this takeover mechanism -set by aspect ratio and enhanced by stronger local alignment -we also employed a continuum model of a bi-phasic active nematic, where we took the two different bacteria types into account with an additional phase field order parameter 𝜙, where 𝜙 > 0 (𝜙 < 0) corresponded to longer (shorter) bacteria regions modelled with a higher (lower) elastic constant and extensile activity (which mimics the dipolar force of division (24,25)). It is well established that both orientational elasticity and extensile division activity are higher for higher aspect ratios (26,27). We observed that even when the front is mostly populated by shorter bacteria, the phase corresponding to the more elongated bacteria eventually overtakes the shorter (Supplementary Fig.…”
Section: Alignment-induced Mechanism Gives Longer Bacteria a Mechanic...supporting
confidence: 58%
“…To emphasise the generic mechanical nature of this takeover mechanism -set by aspect ratio and enhanced by stronger local alignment -we also employed a continuum model of a bi-phasic active nematic, where we took the two different bacteria types into account with an additional phase field order parameter 𝜙, where 𝜙 > 0 (𝜙 < 0) corresponded to longer (shorter) bacteria regions modelled with a higher (lower) elastic constant and extensile activity (which mimics the dipolar force of division (24,25)). It is well established that both orientational elasticity and extensile division activity are higher for higher aspect ratios (26,27). We observed that even when the front is mostly populated by shorter bacteria, the phase corresponding to the more elongated bacteria eventually overtakes the shorter (Supplementary Fig.…”
Section: Alignment-induced Mechanism Gives Longer Bacteria a Mechanic...supporting
confidence: 58%
“…Bacterial cell proliferation is the driving force underpinning mechanical interactions in a colony [25][26][27]. Away from division events, the cell length growth obeys a linear law (with coefficient 𝐺 𝑅 ) modified to include a mechanoresponse 𝜙(𝛿) of the cell to the growing pressure exerted by other cells due to proliferation stresses d𝑙 d𝑡…”
Section: Bacterial Modelmentioning
confidence: 99%
“…In equation (2.4), 𝐺 𝑅 = 10 −7 is a growth rate constant. It has been observed that when colonies grow, the increasing pressure exerted by each cell on its neighbors leads to a slowdown in the cell length growth, akin to a contact inhibition [23,25]; the term in square brackets is a sigmoid function that models such mechanoresponse to the growing pressure, where 𝛼 = 60 represents a scale parameter regulating the steepness of this mechanoresponse, 𝛿 is the total overlap between a cell and its neighbors, and 𝛿 0 = 0.12𝜎 is the inflection point of this dependence. To avoid artificial synchronization effects in cell divisions across the colony, when a cell divides, the two daughter cells differ in length by a random amount with 5% maximum amplitude.…”
Section: 4)mentioning
confidence: 99%
“…The degree of collective orderliness of the pigeon flock at different time points can be revealed by the flock's orderliness graph (Figure 3a), which is obtained using Equation ( 3) in Section 2. The time indices 1 ⃝, 2 ⃝, 3 ⃝ represent periods of significant fluctuations in collective orderliness. The graph facilitates the evaluation of collective behavioral patterns, dynamic changes in flock structure, and the group's stability.…”
Section: Measurement Of Flock Synchronizationmentioning
confidence: 99%
“…Cooperative behavior is frequently observed in biological systems at both micro and macro levels in the natural world. Bacterial colonies [1], fish schools [2], bird flocks [3], and mammal herds [4][5][6] all exhibit collective behavior. The study of collective motion emerged in the 1990s with the advent of computer simulations.…”
Section: Introductionmentioning
confidence: 99%